Psychotropic Medication Use in Children and Adolescents: Review of Outpatient Treatments - Usta, M.B.; Gümüş, Y.Y.; Aral, A.; Say, G.N.; Karabekiroǧlu, K. (Yerkure Tanitim ve Yayincilik, 2018)
Objective: In the literature, children and families have been reported to show high rates of non-adherence to psychopharmacological treatment. This study aimed to investigate psychotropic drug selection, repeat prescription rates, and drug compliance in children who presented to the psychiatry department of a university hospital. Method: Patients examined at the Ondokuz Mayis University Child Psychiatry Outpatient Clinic were included in the study. Patients were retrospectively screened with the Nucleus® system. Results: 12607 patients were included the study, 8889 of whom (70.4%) had received at least one prescription during the follow-up. The mean age of the patients was 12.1±5.0 years and the male sex ratio was 57.4%. The highest-prescribed drug groups were antipsychotics (32.7%) and stimulants (32.5%). A total of 38432 psychotropic drug prescriptions were made. Patients using psychotropic drugs were given prescriptions 4.32 times on average during this time period, while 2356 patients (26.2%) received one prescription. Conclusions: Over the time period of the study, one out of every four patients who used psychotropic medication only received one prescription. Many of the psychotropic drugs used in children and adolescents are part of long-term treatments, and we observed a high rate of non-adherence to psychopharmacological treatment in children and families. For future research, we recommend to include factors affecting treatment adherence in children and families. © 2018, Yerkure Tanitim ve Yayincilik Hizmetleri A.S.
Keywords: Adolescent; Child; Outpatient Treatment; Psychotropic Medication